Kemampuan Unit Usaha Yayasan Nurul Hayat Dalam Menunjang Biaya Operasioanal Lembaga Amil Zakat - Nastiti, Novalia; Mawardi, Imron (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
Amil zaka in zaka institutions has the right as one of eight ashnaf. Their rights are usuallyÂ used by zaka institutions as operational cost. However, not all of the intitutions which manageÂ zaka take amilâs right, one of them is Yayasan Nurul Hayat. This institution does not takeÂ amilâs right and it is independent in its operational cost. To support this operational cost,Â Yayasan Nurul Hayat establish business unit with utilize its profit.This study aimed to discover the capability of business unit in supporting operationalÂ cost of Yayasan Nurul Hayat. This study used a qualitative approach with descriptive caseÂ study method. The selections of informant are using purposive sampling method. DataÂ collection was conducted by semi-structured interviews and documentation. This data isÂ analyzed using descriptive method.The result of this study shows that Yayasan Nurul Hayat Employmentsâ Salary is takenÂ from business unitâs profit. It is also used to give bonus for employments and grow the businessÂ unit of Yayasan Nurul Hayat up. From the result of this study, it can be concluded that theÂ business unit which is developed has great capability to support operational cost of YayasanÂ Nurul Hayat.